Criminal Law Approach in Handling Bullying Cases in Junior High School Enviroments - Andi Ervin Novara Jaya; Gusti Ayu Utami (Journal of Law, Politic and Humanities, 2026)
This study aims to analyze the legal protection approach for victims of bullying and the obstacles that affect its implementation in the school environment. This study uses an empirical legal method with a sociological approach and a normative approach. Data were obtained through interviews with Guidance and Counseling (BK) teachers, the Violence Prevention and Handling Team (TPPK), and students. Data collection methods used include library research and field research. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results show that the legal protection approach for victims of bullying is carried out through two forms of approaches: a preventive approach and a repressive approach. The preventive approach includes a personal approach, special guidance and handling, consultation with experts, and socialization. And, the repressive approach is carried out through mediation, sanctions, legal assistance, and referrals to relevant parties. The implementation of preventive and repressive approaches in schools continues to face various obstacles, including low student understanding, limited capacity of guidance and counseling teachers and the TPPK team, a culture of inaction within schools, limited coordination with external parties, and suboptimal operational systems and policies at the school level. Therefore, strengthening integrated, sustainable, and collaborative implementation is necessary to ensure effective legal protection for victims.